Association of Caribbean States: some institutional aspects - Gill, Henry S. (CARICOM Secretariat GeorgetownGY, 1994)
Examines possible configurations of an Association of Caribbean States Secretariat. Addresses the issue of membership categories and tackles budgetary and financial matters. Deals with the subject of organs and subsidiary bodies and discusses the need for consultation mechanisms. Makes suggestions in regard to a variety of operational procedures and rules.